THE ANALYSIS FORMULATION OF THE LOWEST ASTRONOMICAL TIDE (LAT) BASED ON THE TIME OBSERVATION (THE CASE STUDY OF BENOA WATERS) - Okol Sri Suharyo; Johar Setiadi; Nawanto Budi Sukoco; Kuncoro Kuncoro (JOURNAL ASRO, 2020)
According to the definition of International Hydrographic Organization (IHO) M-13 2005, the LowestAstronomical Tide (LAT) is Internationally used as chart datum, which is used as instruction for measuring thevalidation of high water surface in the Hydro-oceanography survey. It is predicted by tide prediction for 18.61years. This research is observed minimized in one year. In determining of LAT, it will be analyzed by the tideConstanta and prediction analysis.The analysis of tide Constanta will be calculated by the Rayleigh numberingmethod (the smallest quadrat), start on tide data observation for one month, two months, three months, fourmonths, six months until twelve months data of tide observation. Afterward, from that analysis results of t ideConstanta, it can be predicted the tide for 18.61 years. From this result, the prediction will be found thedifference of the LAT value of tide data less than in one year with tide data in one year. Then, from thedifference of LAT values can be analyzed at a significant level by using the statistical approach. From the resultof the LAT calculation by using data observation of tide in one year will be got the LAT position that is 43.3 cm.If comparing with LAT value which uses a variety of data less than in one year, it will result in the level ofsignificant differences. In this case, LAT value thas is calculated by data less than in one year cannot beequated with LAT which is used by observation of tide data in one year.Keywords: LAT, Tide Component, and interval of tide observation.